مقارنة بين قيم سرعة تثفّل الكريات الحمر((ESR وقيم البروتين الارتكاسي (C) في مجموعات مرضية ذات تظاهرات التهابية - رومية, عبد الرحمن; خياط, عماد; عز الدين, وائل (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 300 مريضٍ من مشفى الأسد الجامعي في محافظة اللاذقية بين عامي 2005-2006 وقد وزِّع المرضى على أربع مجموعات، الأولى: الأمراض الإنتانيةالجرثومية، الثانية: الأمراض الرثوانية، الثالثة: الأمراض الدموية، الرابعة: التنشؤات الورمية. وكان الهدف من الدراسة محاولة إيجاد علاقة بين البروتين الارتكاسي (C) وسرعة تثفّل الكريات الحمر عند المجموعات المرضية ذات التظاهرات الإلتهابية. وقد خلصت الدراسة الى النتائج الآتية: في المجموعة الاؤلى كان متوسط سرعة التثفّل 61ملم\ساعة لدى الإناث و58 ملم\الساعة لدى الذكور ومتوسط قيمة البروتين الارتكاسي( (C 53 ملغ\ل. في المجموعة الثانية كان متوسط سرعة التثفّل 55 ملم\الساعة لدى الإناث و48ملم\الساعة لدى الذكور وبلغ متوسط قيمة البروتين الارتكاسي(C) 76ملغ\ل. في المجموعة الثالثة، كان متوسط سرعة التثفّل 60 ملم\الساعة لدى الإناث و67ملم\الساعة لدى الذكور والبروتين الارتكاسي (C ) 82 ملغ\ل، المجموعة الرابعة كان متوسط سرعة التثفّل76ملم \الساعة لدى الإناث و84ملم\الساعة لدى الذكور. أما البروتين الارتكاسي (C ) فقد بلغ متوسط تركيزه 77ملغ\ل. The study depended on 300 patients in AL ASSAD`S University Hospital in Lattakia between the years 2005 and 2006. The patients were separated into four groups: the first group, with infectious diseases; the second group with rheumatoid diseases; the third group with hematological diseases; and the Fourth group with different cancers. The goal of the study was to find a relation among the erythrocyte Sedimentation rate and the C-reactive protein and the groups with inflammatory phenomena. This study reached these results: 1. In the first group, the mid numbers of the erythrocyte Sedimentation rate was 61mlm/h in women and 58 mlm\h in man, and the mid numbers of C - reactive protein was53mgł. 2. The second group had 28 % from the whole numbers of patients; the mid numbers of the erythrocyte sedimentation rate was 55mlm/h women and 48mlm\h in man; and the mid numbers of C- reactive protein was76mgł. 3. The third group had 16 % from the whole numbers of patients; the mid numbers of the erythrocyte Sedimentation rate was 60 mlm/h in women and 67mlm\h in man; and the mid numbers of C - reactive protein was 82mgł. 4. The fourth group had 19.2% from the whole numbers of patients; the mid numbers of the erythrocyte sedimentation rate was76mlm/h in woman and 84mlm\h in man; and the mid numbers of C-reactive protein was 77mgł.